A Different Approach to Work Discipline Models, Manifestations and Methods of Behaviour Modification - Bugdol, Marek (Springer International Publishing, 2018)
'Presented in the form of an exhaustive guide to dealing with issues ranging from compliance enforcement to whistle-blower protection, Marek Bugdol's book is primarily a timely and thorough compendium of solutions useful in the course of management of any organisation, however small or large. Based on the author's thorough engagement with extant literature and full of illustrative examples, the book will be indispensable to students, scholars, and practitioners of management alike.' -Jerzy Kociatkiewicz, University of Sheffield, UK 'This well-written monograph provides coverage of many important issues, including discipline, control and punishment. It is unique in that it links theory and practice. In this book, the models of discipline, self-discipline and organisations without bosses are described. All readers will find much to stimulate their thinking, especially when reading about the methods of behaviour modification.' -Joanna Paliszkiewicz, Professor of Management, Warsaw University of Life Sciences - SGGW, Poland, and Adjunct Professor, University of Vaasa, Finland Providing insight into the currently applied models, basic definitions and functions of work discipline systems within organisations, this book analyses the risks, limitations and the potential of developing organisational discipline structures. It examines various examples and manifestations of unethical and criminal behaviour in the workplace and places special emphasis on informal pubishment structures and the conditions under which they occur. Difficult topics are tackled including sabotage, theft, bullying, financial fraud, sexual harrassment and blackmail. Assessing the effectiveness of work discipline systems upon organisational behaviour, this innovative book offers practical solutions for managers, as well as new approaches for those studying human resource management. Marek Bugdol is Professor of Management and Head of the Chair of Quality Management at Jagiellonian University, Poland. He specialises in the social issues related to management, primarily in values and organisational behaviour. He worked for many years in an international manufacturing company, starting at the position of manual labourer and finishing as the marketing department manager. He has also held managerial positions in local government institutions. .